Optimization of Enzymatic Hydrolysis for Preparation of Shrimp Flavor Precursor Using Response Surface Methodology. Issue 4 (18th July 2014) - Guo, Xiaoxun; Han, Xiaoxiang; He, Yanfei; Du, Huan; Tan, Zhongqin
Abstract Response surface methodology was successfully applied to optimize the process parameters for flavor precursor – enzymolysis liquor by enzymolysis technology using Penaeus chinensis waste as raw material. The parameters, namely, enzyme concentration, reaction temperature and initial pH, on the degree of hydrolysis (DH) were optimized using central composite rotatable design. The obtained optimum conditions were: initial pH value of 6.5, Dispase concentration 2.0 wt %, reaction temperature 57C and hydrolysis time 3 h with material : water ratio 1:10. Under the optimized conditions, the DH reached 57.65%. In the hydrolyzate, the content of free amino acids and essential amino acids was 29.67 and 11.30 mg/mL, respectively. This product exhibited strong delicious flavor, so it was suitable for flavor seasoning. Practical Applications The present work was taken up to establish the optimum conditions for extraction of the flavor precursor from hydrolyzing Penaeus chinensis waste by Dispase and obtain enzymolysis liquid that is rich in amino acids and polypeptide, which could improve the value of shrimp waste.